Geomagnetically induced currents around the world during the 17 March 2015 storm. Issue 10 (25th October 2016) - Carter, B. A.; Yizengaw, E.; Pradipta, R.; Weygand, J. M.; Piersanti, M.; Pulkkinen, A.; Moldwin, M. B.; Norman, R.; Zhang, K.
Abstract: Geomagnetically induced currents (GICs) represent a significant space weather issue for power grid and pipeline infrastructure, particularly during severe geomagnetic storms. In this study, magnetometer data collected from around the world are analyzed to investigate the GICs caused by the 2015 St. Patrick's Day storm. While significant GIC activity in the high‐latitude regions due to storm time substorm activity is shown for this event, enhanced GIC activity was also measured at two equatorial stations in the American and Southeast Asian sectors. This equatorial GIC activity is closely examined, and it is shown that it is present both during the arrival of the interplanetary shock at the storm sudden commencement (SSC) in Southeast Asia and during the main phase of the storm ∼10 h later in South America. The SSC caused magnetic field variations at the equator in Southeast Asia that were twice the magnitude of those observed only a few degrees to the north, strongly indicating that the equatorial electrojet (EEJ) played a significant role. The large equatorial magnetic field variations measured in South America are also examined, and the coincident solar wind data are used to investigate the causes of the sudden changes in the EEJ ∼10 h into the storm. From this analysis it is concluded that sudden magnetopause current increases due to increases in the solar wind dynamic pressure, and the sudden changes in the resultant magnetospheric and ionospheric current systems, are the primary drivers of equatorial GICs. Key Points: GICs measured around the world during the 17 March 2015 storm are examined Enhanced GIC activity near the equator is observed both at the start and during the storm in different longitude sectors Solar wind data indicate that sudden changes in the solar wind dynamic pressure caused the enhanced equatorial GICs